TRANSFORMASI SERTIFIKASI ELEKTRONIK: SOLUSI DAN TANTANGAN PENDAFTARAN TANAH DARI PERSPEKTIF PRAKTISI - Karmila Sari Sukarno,; Reky Nurviana, (Journal of Innovation Research and Knowledge, 2025)
The transition of the land registration system from conventional methods to digital forms is a strategic step in the modernization of Indonesia's land administration. This policy is based on the Cipta Kerja Law and Minister of ATR/BPN Regulation No. 3 of 2023, which aims to improve efficiency, transparency, and legal certainty in land services. This study analyzes the challenges faced by practitioners, particularly Notaries and PPATs. Through a qualitative approach, the study identifies the main challenges, including inadequate updating of legal and physical data, limitations in technological infrastructure, low digital literacy among the public, and potential cybersecurity threats. Recommendations for improving the electronic land certification system include the need to refine the system and enhance human resource capacity, human resources, strengthening infrastructure and information technology, implementing blockchain technology to ensure data security, and conducting systematic socialization and digital literacy programs. This system transformation, if supported by a comprehensive risk mitigation strategy, has the potential to accelerate bureaucratic reform and improve the national investment climate.